Learning to Write Short-Story Text with a Cooperative Integrated Model Reading and Composition based on SHS Learners’ Cognitive Styles - Adefia, Lida; Subyantoro, Subyantoro; Wagiran, Wagiran (Universitas Negeri Semarang, 2021)
Learning to write short-story text expects the learners to capable of explaining a process of certain phenomenon occurrence. Therefore, an appropriate learning model is needed based on the learners’ cognitive styles. This research explained the effectiveness of short-story text learning with the CIRC model based on the eleventh graders’ cognitive styles. The research design was a one-group pretest-posttest. The sample was taken with purposive sampling. The instruments of data analysis techniques were validity and reliability tests. The samples were examined with normality and homogeneity tests. The final data analysis was a t-test to determine the effectiveness comparison of the cognitive style-based short-story writing learning. The findings showed the average score of FD-styled learners was 82.42, 79.13 for the moderate-styled learners, and 86.48 for FI-styled learners. Theoretically, the findings could be implemented to enrich the educational research and knowledge of writing short-story text.